Pengembangan Model Implementasi Agile Governance pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu di Provinsi Sulawesi - Puji Lestari, Nana; Fajar Putera, Arifin; Hasniati, Hasniati; Rusdi, Muhammad; Nara, Nurdin; Amalia, Ayu (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study examines the implementation of Agile Governance in the Investment and One-Stop Service Offices (DPMPTSP) across Sulawesi provinces, addressing rapid regulatory shifts under the OSS-RBA system and the absence of an empirically validated implementation model. The study aims to analyze the effects of environmental factors, agile capabilities, and governance capabilities on business operations and value delivery, and to develop an evidence-based implementation model. A sequential explanatory mixed-methods design was applied. The quantitative phase surveyed 380 civil servants in South Sulawesi, Central Sulawesi, and West Sulawesi and was analyzed using SEM-PLS. The qualitative phase, conducted in West Sulawesi, involved in-depth interviews, performance document analysis (SKM, SAKIP, budget absorption, investment realization), and NVivo-based thematic coding. Results show that environmental factors do not directly affect business operations (E→B not significant), but their influence emerges through agile and governance capabilities. The strongest relationship is governance capability → value delivery (G→R; highest F²), followed by agile capability → governance capability (A→G). Qualitative findings confirm that high SKM scores (“Very Good”), SAKIP grades (“A”), and budget absorption above 90% reflect administrative compliance rather than adaptive agility. Key barriers include hierarchical bureaucracy, regulatory instability, and uneven human resources competencies. The study proposes an Agile Governance implementation model emphasizing the simultaneous strengthening of agile and governance capabilities, flexible cross-unit coordination, real-time data utilization, and stronger feedback loops with business actors. Policy implications include integrating adaptiveness indicators into performance management, enhancing data-driven service control units, and building adaptive capacities among civil servants in licensing and investment services.